2006
DOI: 10.1203/01.pdr.0000203563.37626.77
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pathways and Specification of Intrapulmonary Stem Cells

Abstract: ABSTRACT:Tissues have the capacity to maintain a homeostatic balance between wear-and-tear and regeneration. Repair of nonlethal injury also activates cell proliferation to repopulate the injured sites with appropriate cell types and to restore function. Although controversial, the source of the material appears to be at least partly from pools of unique, multipotent stem cells that reside in specialized locations referred to as "niches." Molecular interactions between the niche and the intracellular factors w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…Different from other tissue stem cells, only rare BASCs may be activated to participate in epithelial repair after depletion of so-called ''transit-amplifying cells,'' cells characterized as progenies of tissue stem cells with proliferative capacity (69,165,167). Recently, the involvement of WNT signaling in lung stem cell maintenance and activation has been pointed out (168)(169)(170). Zhang and colleagues (168) demonstrated that the transcription factor, GATA6, influences the temporal appearance and number of BASC in the lung by regulating WNT signaling.…”
Section: The Wnt Signaling Pathway-stem Cell Maintenancementioning
confidence: 99%
“…Different from other tissue stem cells, only rare BASCs may be activated to participate in epithelial repair after depletion of so-called ''transit-amplifying cells,'' cells characterized as progenies of tissue stem cells with proliferative capacity (69,165,167). Recently, the involvement of WNT signaling in lung stem cell maintenance and activation has been pointed out (168)(169)(170). Zhang and colleagues (168) demonstrated that the transcription factor, GATA6, influences the temporal appearance and number of BASC in the lung by regulating WNT signaling.…”
Section: The Wnt Signaling Pathway-stem Cell Maintenancementioning
confidence: 99%
“…Regardless, stem cells play an essential role in the development and maturity of many organ systems including the central nervous, respiratory, cardiovascular, haematologic, immunologic and endocrine systems long before birth [97][98][99][100][101][102]. The aetiology of many diseases of the newborn is related to delayed development and immaturity.…”
Section: Nature's First Stem Cell Transplant Occurs At Birth When Thementioning
confidence: 99%
“…Activation of fibroblasts in response to injury mediates the reparative response of the epithelium (3,(7)(8)(9)(10)(11), and the roles of fibroblasts in compensatory lung growth, realveolarization following partial pneumonectomy (PNX) has been noted in several species (12)(13)(14)(15)(16)(17)(18). The availability of transgenic mice nowadays provides the tools for extensive characterization of the cellular and molecular mechanisms responsible for compensatory lung regrowth after PNX.…”
Section: Introductionmentioning
confidence: 99%